AuPd/Fe3O4-based three-dimensional electrochemical system for efficiently catalytic degradation of 1-butyl-3-methylimidazolium hexafluorophosphate. (20th December 2015) - Qin, Yinghua; Sun, Meng; Liu, Huijuan; Qu, Jiuhui
Graphical abstract: Highlights: AuPd/Fe3 O4 3D system had very good performance in catalytic degradation of [BMIM] ILs. AuPd/Fe3 O4 promotes the in situ electrocatalytic generation of H2 O2 and Fe species. The degradation rule of BMIM was well followed the classic AFT model. The H2 O2 inflection point suggested the optimal effectiveness of 3D system. The recyclable AuPd/Fe3 O4 had good catalytic stability for wastewater treatment. Abstract: Ionic liquids (ILs) have been reported to be toxic and harmful to aquatic and terrestrial organisms, thus it is imperative to remove the residual ILs in various effluents. In this work, a three-dimensional (3D) electrocatalytic system with synthesized AuPd/Fe3 O4 nanoparticles (NPs) as particle electrodes (PEs) was established for the degradation of typical 1-butyl-3-methylimidazolium ([BMIM]) based ILs. The as-synthesized AuPd/Fe3 O4 possessed preferable electrochemical properties for in situ supplement of H2 O2 and renewable Fe species. This 3D electrocatalytic system exhibited excellent performance with 100% removal rate of BMIM in 90 min under 120 mA, pH 3, and 1 g/L dosage of AuPd/Fe3 O4 NPs. Kinetics study revealed that the degradation rule of BMIM well followed the anodic Fenton treatment (AFT) model, in which the variation of the degradation rate was positively correlated with that of dissolved Fe 2+, while significantly differed from the evolution of H2 O2 . Particularly, the appearance of the H2 O2 inflection point suggested the optimal effectiveness of AuPd/Fe3 O4 -based 3D electrocatalysis. During this electrocatalytic process, the active HO was produced over the AuPd/Fe3 O4 PEs, thereby initiated the highly efficient degradation of BMIM into 1-butyl-3-methyl-2, 4, 5-trioxoimidazolidine, 1-butyl-3-methylurea and N-butyl-formamide as main intermediates. The electrocatalytic stability of the AuPd/Fe3 O4 PEs over seven times further indicated the potential applicability for organic wastewater treatment.